The GABAergic system in prefrontal cortex and hippocampus modulates context-related extinction learning and renewal in humans. - Lissek, Silke; Golisch, Anne; Glaubitz, Benjamin; Tegenthoff, Martin (Brain Imaging & Behavior, 2017)
Context-related extinction learning and renewal in humans is mediated by hippocampal and prefrontal regions. Renewal is defined as the reoccurrence of an extinguished response if the contexts present during extinction learning and recall differ. Animal studies implicate hippocampal γ-aminobutyric acid (GABA) A receptors in extinction and renewal. However, human studies on GABAergic mechanisms in extinction learning are lacking. In this fMRI study, we therefore investigated the role of the GABAergic system in context-related extinction learning and renewal. Participants treated with the GABA A agonist lorazepam prior to extinction learning were impaired in encoding changed associations during extinction learning, regardless of context, and in retrieving extinction associations during recall. In contrast, retrieval of associations learned during acquisition was largely unaffected, which led to reduced genuine renewal, since acquisition associations were retrieved context-independently. These deficits, which were presumably due to weak encoding of extinction associations, were related to altered BOLD activation in regions relevant for context processing and retrieval, as well as response selection: reduced activation in bilateral PFC and hippocampus during extinction learning and recall, and increased ventromedial/orbitofrontal cortex activation during recall. Our findings indicate that the GABergic system is involved in context-related extinction learning and recall in humans, by modulating hippocampus-based context processing and PFC-based processing of changed associations and subsequent response selection.